F-box protein MAX2 has dual roles in karrikin and strigolactone signaling in Arabidopsis thaliana - Nelson, D.; Scaffidi, A.; Dun, E.; Waters, M.; Flematti, G.; Dixon, Kingsley; Beveridge, C.; Ghisalberti, E.; Smith, S. (2011)
Smoke is an important abiotic cue for plant regeneration in postfire landscapes. Karrikins are a class of compounds discovered in smoke that promote seed germination and influence early development of many plants by an unknown mechanism. A genetic screen for karrikin-insensitive mutants in Arabidopsis thaliana revealed that karrikin signaling requires the F-box protein MAX2, which also mediates responses to the structurally-related strigolactone family of phytohormones. Karrikins and the synthetic strigolactone GR24 trigger similar effects on seed germination, seedling photomorphogenesis, and expression of a small set of genes during these developmental stages. Karrikins also repress MAX4 and IAA1 transcripts, which show negative feedback regulation by strigolactone. We demonstrate that all of these common responses are abolished in max2 mutants. Unlike strigolactones, however, karrikins do not inhibit shoot branching in Arabidopsis or pea, indicating that plants can distinguish between these signals. These results suggest that a MAX2-dependent signal transduction mechanism was adapted to mediate responses to two chemical cues with distinct roles in plant ecology and development.